The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18235/0003104
|View full text |Cite
|
Sign up to set email alerts
|

El efecto de la doble escolaridad sobre la participación laboral femenina en República Dominicana

Abstract: En este trabajo se analiza la incidencia de un aumento en las horas escolares de los niños sobre la oferta laboral femenina en República Dominicana. La reciente política de Jornada Escolar Extendida (JEE) duplica las horas escolares en el sistema público dominicano, lo cual podría generar un cambio en las decisiones laborales de los hogares beneficiados. En particular, esta iniciativa relaja las restricciones que enfrentan las mujeres para participar en el mercado de trabajo, teniendo en cuenta que las madres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…and non-cognitive outcomes. Existing studies on the e↵ects of FTS concentrate on short-term low-stakes test scores (Cerdan-Infantes and Vermeersch, 2007;Bellei, 2009;Dias Mendes, 2011;Xerxenevsky, 2012;Llambí, 2013;Orkin, 2013;Almeida et al, 2016;Hincapie, 2016;Cabrera-Hernández, 2020;Agüero et al, 2021;Padilla-Romo, 2022), mothers and grandmothers' labor supply (Nemitz, 2015;Contreras and Sepúlveda, 2017;Padilla-Romo and Cabrera-Hernández, 2019;Cabrera-Hernández and Padilla-Romo, 2020;Garganta and Zentner, 2020;Berthelon et al, 2022), child labor (Kozhaya and Flores, 2022), divorce (Padilla-Romo et al, 2022), teen pregnancy, and youth crime (Berthelon and Kruger, 2011). Outcomes in the long run have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…and non-cognitive outcomes. Existing studies on the e↵ects of FTS concentrate on short-term low-stakes test scores (Cerdan-Infantes and Vermeersch, 2007;Bellei, 2009;Dias Mendes, 2011;Xerxenevsky, 2012;Llambí, 2013;Orkin, 2013;Almeida et al, 2016;Hincapie, 2016;Cabrera-Hernández, 2020;Agüero et al, 2021;Padilla-Romo, 2022), mothers and grandmothers' labor supply (Nemitz, 2015;Contreras and Sepúlveda, 2017;Padilla-Romo and Cabrera-Hernández, 2019;Cabrera-Hernández and Padilla-Romo, 2020;Garganta and Zentner, 2020;Berthelon et al, 2022), child labor (Kozhaya and Flores, 2022), divorce (Padilla-Romo et al, 2022), teen pregnancy, and youth crime (Berthelon and Kruger, 2011). Outcomes in the long run have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Our study contributes to the specific analysis of the effects of the JEE. Garganta and Zentner (2021) showed that this introduction of longer school days in the country had a positive impact on female labor force participation, particularly for low-educated women who are not the primary earner in the household. We add up to this literature by analyzing its impacts on risky behaviors among adolescents, particularly on the prevalence of teenage fertility.…”
Section: Introductionmentioning
confidence: 99%